2012
DOI: 10.1186/1756-0500-5-383
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perioperative oxygen fraction on pulmonary function after abdominal surgery: a randomized controlled trial

Abstract: BackgroundA high perioperative inspiratory oxygen fraction (FiO2) may reduce the frequency of surgical site infection. Perioperative atelectasis is caused by absorption, compression and reduced function of surfactant. It is well accepted, that ventilation with 100% oxygen for only a few minutes is associated with significant formation of atelectasis. However, it is still not clear if a longer period of 80% oxygen results in more atelectasis compared to a low FiO2.Our aim was to assess if a high FiO2 is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 37 publications
(54 reference statements)
0
37
0
Order By: Relevance
“…3B) (table 3). 55,56,60,61,63,64,69,70,72 Six articles reported on atelectasis using chest radiographs and/or thoracic computed tomography scans for diagnosis (table 4); however, two of those 69,70 were subgroup analyses reporting on the same outcomes as the original larger study. 63 Thus, data from four trials, two small 56,60 and two large, 63,64 could be combined (fig.…”
Section: Perioperative Medicinementioning
confidence: 95%
See 3 more Smart Citations
“…3B) (table 3). 55,56,60,61,63,64,69,70,72 Six articles reported on atelectasis using chest radiographs and/or thoracic computed tomography scans for diagnosis (table 4); however, two of those 69,70 were subgroup analyses reporting on the same outcomes as the original larger study. 63 Thus, data from four trials, two small 56,60 and two large, 63,64 could be combined (fig.…”
Section: Perioperative Medicinementioning
confidence: 95%
“…55,60,69 In one, 55 there was an evidence of statistically significant worsening of the intraoperative Pao 2 / FIo 2 ratio in patients receiving 100% FIo 2 (use of positive end-expiratory pressure and postoperative Pao 2 /FIo 2 ratio was not reported). The two other studies failed to show any detrimental effect on the postoperative Pao 2 /FIo 2 ratio with supplemental oxygen, 60,69 despite the use of 100% oxygen and no positive end-expiratory pressure in one trial. 60 Three small studies reported on lung function (table 4).…”
Section: Perioperative Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…10 Another subgroup study of the PROXI Trial involving 35 patients showed no significant difference in change in oxygenation index or functional residual capacity when 80% oxygen was administered than when 30% oxygen was used. 36 Less evidence of the effect of ventilation with high oxygen is available in obese patients, but morbidly obese patients are more prone to perioperative atelectasis formation, and the atelectasis remains unresolved for a longer period after surgery than occurs in nonobese patients. 1 One recent study of 142 moderately obese patients found a minimal reduction in postoperative lung function when patients were given 80%, compared with 40%, oxygen during minor peripheral surgery.…”
Section: Discussionmentioning
confidence: 99%